(untitled) (Journal of Building and Road Research, 2021)
Population and urbanization growth caused an increase in the amount of solid waste generated. The 7- cleaning projects responsible for the collection and transport of Solid Waste (SW) for Khartoum State are currently unable to perform their duties to the level expected with the result that the city is unclean and there is considerable impact on the environment and health of the citizens. There is a need to quantify these general observations. This is done by the use of Key Performance Indicators (KPIs). This paper aims to identify a set of KPIs for measuring the performance of Solid Waste Management (SWM) system at the collection and transport level. The study targeted the 7-cleaning projects -in particular, the operation department responsible for collection and transport of SW for each cleaning project together with the operation department at the Supervisory Authority of Cleaning Khartoum (SACKH) which supervises their work. List of 28 potential performance indicators have been identifed through the literature review. A survey questionnaire was conducted on a randomly selected sample of the operation departments . The statistical analysis of the collected responses was provided in 11 signifcant KPIs. It is hoped that the results of this study will become the frst step in developing Integrated KPIs for enhancing the performance of SWM of Khartoum state- the capital of Sudan.